KAJIAN LITERATUR PERBEDAAN BIMBINGAN LITERASI DAN BIMBINGAN NUMERASI TERHADAP KEMAMPUAN BELAJAR SISWA SEKOLAH DASAR - Chusnah, Asmaul; Bahtiar, Reza Syehma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study entitled "Literary Study of Differences in Literacy Guidance and Numeracy Guidance on Learning Ability of Elementary School Students." The purpose of this study was to determine and analyze the results of literacy and numeracy guidance on the learning abilities of elementary school students. The discussion of this journal is focused on research with a quantitative approach. The results of the study show that literacy and numeracy tutoring is very influential for students' learning abilities. This influence comes from various factors including internal factors and external factors. Based on the literature review conducted, it was found that literacy guidance has a significant role in improving the reading comprehension, information analysis, and verbal communication skills of elementary school students. Students who receive literacy guidance tend to have better abilities in understanding learning materials as a whole.Numeracy guidance focuses on developing logical thinking skills, quantitative analysis, and mathematical problem solving. Students who receive numeracy guidance show improvements in their ability to calculate and apply mathematical concepts in everyday contexts.The main difference between the two types of guidance lies in the learning approach and the types of skills developed. However, both complement each other in improving the quality of student learning holistically.